Peer Counseling in Educational Settings: Analyzing Its Effectiveness in Addressing Anxiety Among College Students Using Pretest-Posttest Design - Endang Pasaribu (P3M STAI Kuningan, 2025)
College student mental health has reached crisis proportions, with anxiety disorders now affecting approximately 30-40% of students globally. The need for effective interventions to address anxiety in higher education settings is urgent. This study aims to examine the effectiveness of peer counseling interventions in reducing anxiety levels among college students over an 8-week intervention period, using a pretest-posttest design. A single-group pretest-posttest design was used, with 85 college students exhibiting elevated anxiety (Beck Anxiety Inventory scores > 16). The students participated in structured peer counseling sessions twice weekly. Anxiety levels were assessed using the Beck Anxiety Inventory (BAI) at baseline and post-intervention. The results demonstrated statistically significant reductions in anxiety scores from pretest (M=24.6, SD=6.2) to posttest (M=16.3, SD=5.8), t(84)=12.45, p<.001, d=1.35, indicating a large effect size. Qualitative feedback revealed high participant satisfaction with the accessibility, relatability, and non-judgmental atmosphere of peer support. Peer counseling is an effective, cost-efficient complement to professional mental health services in higher education settings, particularly for addressing mild to moderate anxiety. Implications for campus mental health programming and recommendations for peer counselor training are discussed.